Characterization of heat transfer process in selective laser melting - Ong, Zong Wei. (2010)
This report serves as a documentation of the work and research that the student has accomplished for his final year project on the Characterization of Heat Transfer Process in Selective Laser Melting. The report consists of a literature review on the theory of Additive Manufacturing and its various techniques. Six different machines across varying additive manufacturing concepts are brought together and examined in detail. One of these machines, M2 Cusing from Concept Laser is selected to produce specimens for this study. All specimens are made of AlSi10Mg alloy.